STUDENT' CRITICAL THINKING PROFILE THROUGH MODEL OF GROUP INVESTIGATION LEARNING (GI) ON MOTION SYSTEM CONCEPT - Muhammad Billy; Mila Ermila Hendriyani; Vica Dian Aprelia (Universitas Sultan Ageng Tirtayasa, 2017)
This research aims to determine student’s critical thinking ability profile through Group Investigation (GI) learning model on the biological motion systems concept at SMAN 7 Kota Serang. This research used a descriptive method. The population in this research were students of class XI IPA at SMAN 7 Kota Serang and sample were class XI IPA 1 which taken by simple random sampling technique. The data was collected by using essay test to determine student’s critical thinking ability. The result showed that student’s critical thinking ability of SMA Negeri 7 Kota Serang classically include in very critical category as much as 85,20%. Distribution of students in each category of critical thinking ability is 58.82% categorized as critical, 35.29% are very critical, and 5.88% are quite critical.